Identification of low resistivity layers in the “N” geothermal field using 2D magnetotelluric inversion modelling - Nabil Bawahab; Udi Harmoko; Tony Yulianto; Irvan Ramadhan (Diponegoro University Semarang Indonesia, 2020)
Magnetotelluric research in the “N” geothermal field has been carried out to see the subsurface detail in the “N” geothermal field. 2D inversion model is generated by secondary data from magnetotelluric data collection in the form of time series data to become 2D models. Magnetotellurics method is used to identify geothermal system components, especially identifying layers with low resistivity values (2 Ω.m - 10 Ω.m) or also called as the cap rock which is seen with a very contrasting color difference compared to the surrounding layers. There are manifestations on the “N” geothermal field which reinforce the assumption that there is a geothermal system in this area. This research begins by processing time series data to become apparent resistivity and phase data. Time series data processing in this study uses several processing methods to produce better apparent resistivity and phase data. The final result of this study is a 2D model that illustrates the contour of the resistivity value of rocks laterally or vertically. 2D model interpretation in this study identified the cap rock layer with low resistivity distribution (2 Ω.m - 10 Ω.m), the medium resistivity zone identified as the reservoir layer (11 Ω.m - 70 Ω.m), and the resistive zone which has high resistivity value (more than 70 Ω.m).